Mutations in MAB21L2 result in ocular Coloboma, microcornea and cataracts. - Brett Deml; Ariana Kariminejad; Razieh H R Borujerdi; Sanaa Muheisen; Linda M Reis; Elena V Semina (PLoS Genetics, 2015)
Ocular coloboma results from abnormal embryonic development and is often associated with additional ocular and systemic features. Coloboma is a highly heterogeneous disorder with many cases remaining unexplained. Whole exome sequencing from two cousins affected with dominant coloboma with microcornea, cataracts, and skeletal dysplasia identified a novel heterozygous allele in MAB21L2, c.151 C>G, p.(Arg51Gly); the mutation was present in all five family members with the disease and appeared de novo in the first affected generation of the three-generational pedigree. MAB21L2 encodes a protein similar to C. elegans mab-21 cell fate-determining factor; the molecular function of MAB21L2 is largely unknown. To further evaluate the role of MAB21L2, zebrafish mutants carrying a p.(Gln48Serfs*5) frameshift truncation (mab21l2Q48Sfs*5) and a p.(Arg51_Phe52del) in-frame deletion (mab21l2R51_F52del) were developed with TALEN technology. Homozygous zebrafish embryos from both lines developed variable lens and coloboma phenotypes: mab21l2Q48Sfs*5 embryos demonstrated severe lens and retinal defects with complete lethality while mab21l2R51_F52del mutants displayed a milder lens phenotype and severe coloboma with a small number of fish surviving to adulthood. Protein studies showed decreased stability for the human p.(Arg51Gly) and zebrafish p.(Arg51_Phe52del) mutant proteins and predicted a complete loss-of-function for the zebrafish p.(Gln48Serfs*5) frameshift truncation. Additionally, in contrast to wild-type human MAB21L2 transcript, mutant p.(Arg51Gly) mRNA failed to efficiently rescue the ocular phenotype when injected into mab21l2Q48Sfs*5 embryos, suggesting this allele is functionally deficient. Histology, immunohistochemistry, and in situ hybridization experiments identified retinal invagination defects, an increase in cell death, abnormal proliferation patterns, and altered expression of several ocular markers in the mab21l2 mutants. These findings support the identification of MAB21L2 as a novel factor involved in human coloboma and highlight the power of genome editing manipulation in model organisms for analysis of the effects of whole exome variation in humans.